Proposed Performance Management System Implementation With Integrated Performance Management System (IPMS) For PT. Pusatex - Muhammad Fahmi Shahab (UniSadhuGuna Business School, 2023)
The aim of this journal research is to propose the implementation of a performance management system with a focus on the Integrated Performance Management System (IPMS) at PT. Pusatex. Recognizing the importance of a robust performance management framework, the proposed system aims to address key challenges within the company, including traditional marketing methods, the absence of Key Performance Indicators (KPIs) in the company's system, and inefficiencies in the use of machinery and production tools. By implementing IPMS, the goal is to enhance the overall company performance, align business objectives, and foster a culture of continuous improvement. The primary objective is to shape a dynamic and responsive performance management system that not only addresses current challenges but also positions PT. Pusatex to build an effective performance management system to compete with global competitors.